Morphometric cranial standards for sex estimation of a population in two ethnic groups in Southwest Iran - Forouzan Absalan; Ali Reza Eftekhari Moghadam; Jafar Rezaian (Translational Research in Anatomy, 2023)
Background: This study aimed to evaluate the cephalometric landmarks, cranial measurements, and cephalic index based on geographical and ethnic characteristics to make a database for the southwest Iranian population. Method: In this analytical cross-sectional study, different anatomic criteria were collected from head MRI images. The anthropometric measures taken included the maximum cranial length, maximum cranial height, maximum cranial breadth, cranial base length, foramen magnum length, upper facial height, lower facial height, foramen magnum breadth, bizygomatic breadth, orbital breadth, nasion-opisthion. The categorization of the head shape was based on the cephalic index. The cranial index was calculated using the equation ([maximum cranial breadth/maximum cranial length] × 100). These assessments were compared to define sexual dimorphism and inter-population variation in size and shape. Results: Sexual dimorphism existed in all cephalometric data except the cephalic index. The measurements comparisonin ethnicities showed that only (eu–eu) differs significantly between the two groups, which is 2,253 mm less in the Arab population compared to the Lur population (P value = 0.022). The cephalic index in males and females was found to be 73.66 and 75.08, respectively. Accordingly, 53.99% were dolichocephalic, 30.06% were mesocephalic, 14.11% were brachycephalic, and 1.84% were hyperbrachycephalic. The shape of the head had no relation to ethnicity but was related to sex (P value = 0.045). Conclusion: It is shown that cephalometric data can be used as diagnostic criteria to determine sex and ethnicity in the southwest Iranian population. It should be further verified on a greater sample size that evaluates more study age distribution.